Cycling performance of lithium-ion polymer cells assembled with a cross-linked composite polymer electrolyte using a fibrous polyacrylonitrile membrane and vinyl-functionalized SiO2 nanoparticles - Shin, Won-Kyung; Yoo, Ji Hyun; Choi, Wonchang; Chung, Kyung Yoon; Jang, Seung Soon; Kim, Dong-Won (ROYAL SOC CHEMISTRY, 2015)
Vinyl-functionalized SiO2 nanoparticles were synthesized and uniformly dispersed on the surface of a fibrous polyacrylonitrile (PAN) membrane for use as cross-linking sites. A composite polymer electrolyte was prepared by in situ cross-linking between vinyl-functionalized SiO2 particles on the PAN membrane and the electrolyte precursor containing tri(ethylene glycol) diacrylate. The cross-linked composite polymer electrolyte effectively encapsulated the electrolyte solution without leakage. It exhibited good thermal stability as well as favorable interfacial characteristics toward electrodes. Lithium-ion polymer cells composed of a graphite negative electrode and a LiNi(0.)8Co(0.15)Al(0.0)5O(2) positive electrode were assembled with the in situ cross-linked composite polymer electrolyte. The cells with cross-linked composite polymer electrolytes using the fibrous PAN membrane and vinyl-functionalized SiO2 particles exhibited high discharge capacity and good capacity retention at both ambient temperature and elevated temperature.
Keywords: RECHARGEABLE BATTERIES; LINKING AGENT; SOLAR-CELLS; LIQUID; SPECTROSCOPY; MECHANISM; KINETICS; FILLERS; OXIDE); SILICA